Firms and flexibility - Bart Hobijn; Aysegül Sahin (Federal Reserve Bank of New York, 2007)
We study the effects of labor market rigidities and frictions on firm-size distributions and dynamics. We introduce a model of endogenous entrepreneurship, labor market frictions, and firm-size dynamics with many types of rigidities, such as hiring and firing costs, search frictions with vacancy costs, unemployment benefits, firm entry costs, and a tax wedge between wages and labor costs. We use the model to analyze how each rigidity explains firm-size differentials between the United States and France. We find that when we include all rigidities and frictions except hiring costs and search frictions, the model accounts for much of the firm-size differentials between the United States and France. The addition of search frictions with vacancy costs generates implausibly large differentials in firm-size distributions.
Keywords: C78; D21; E24; J6; L26; 330; Labor market; Corporations - Finance; Business enterprises - Finance; Employment; Unemployment; Betriebsgröße; Arbeitsmarkt; Arbeitsplatzsuchmodell; Vergleich; Frankreich; USA